2014
DOI: 10.1515/cclm-2014-0194
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the Spine Deformity Index, biochemical parameters of bone metabolism and vascular calcifications: results from the Epidemiological VERtebral FRACtures iTalian Study (EVERFRACT) in dialysis patients

Abstract: We conclude that the severity of VFs was associated with age, atherogenic factors and bone metabolism markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In fact, higher total BGP levels were found associated with lower abdominal aortic calcification progression rate and lower mortality in a 10 year-long prospective study in elderly Caucasian subjects, showing total BGP as an independent factor of cardiovascular risk and mortality (17). Moreover, in the hemodialysis population we showed that low levels of total-BGP are associated with vertebral fractures, aortic and iliac calcifications (5). Finally, a recent review reported low BGP levels as a biomarker of abdominal aortic calcification in patients with diabetes (18).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In fact, higher total BGP levels were found associated with lower abdominal aortic calcification progression rate and lower mortality in a 10 year-long prospective study in elderly Caucasian subjects, showing total BGP as an independent factor of cardiovascular risk and mortality (17). Moreover, in the hemodialysis population we showed that low levels of total-BGP are associated with vertebral fractures, aortic and iliac calcifications (5). Finally, a recent review reported low BGP levels as a biomarker of abdominal aortic calcification in patients with diabetes (18).…”
Section: Discussionmentioning
confidence: 60%
“…BGP also has a protective role in vascular calcifications in humans (5), acting under the genetic control of vitamin D. Vitamin D deficiency is highly prevalent in CKD patients, suggesting that the protective role of vitamin D on vascular calcification (6) may be mediated by a reduced expression of BGP and other vitamin K dependent proteins involved in calcification pathways, such as Matrix Gla Protein, a potent inhibitor of vascular calcifications (7). Levels of BGP in DM patients on hemodialysis (HD) have been poorly described.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, a 10 years prospective study in elderly Caucasian men showed that BGP levels might be an independent indicator of cardiovascular risk and mortality, with higher total BGP concentrations being associated with lower abdominal aortic calcification (AAC) progression rate and lower mortality [18]. Moreover, we showed that low levels of BGP are associated to vertebral fracture (VF), aortic and iliac calcifications [19].…”
Section: Discussionmentioning
confidence: 75%
“…Consistently, we found that PK deficiency was the strongest predictor of vertebral fractures in hemodialysis patients [65]. Prevalence of vertebral fractures was 55%, with a significant association between severity of fractures and lower levels of total BGP [66]. Currently, there is very little literature on the role of vitamin K supplementation in osteoporosis prevention in men and women.…”
Section: Discussionmentioning
confidence: 81%